PENGARUH SPIRITUALITAS ISLAMI DI TEMPAT KERJA TERHADAP KOMITMEN NORMATIF DENGAN KARAKTERISTIK INDIVIDU SEBAGAI VARIABEL MODERATOR - Istianah, Lailatul; Kistyanto, Anang (IQTISHODUNA, 2016)
This study was to analyze the effect of workplace Islamic spirituality, normative commitment, andindividual characteristics, as well as the moderating role of individual characteristics on workplace Islamicspirituality to normative commitment. Sample of this study were all nurses of the RSI Darus Syifa Surabayatotaling 67 nurses to 66 nurses from the calculation questionnaire back to the processed. Methods of thestatistical analysis that used were SEM Partial Least Square (PLS) with smartPLS 2.0 software. The result ofthis research explained that workplace Islamic spirituality positive and significant effect on normativecommitment. Individual characteristics not moderate the effect of workplace Islamic spirituality to normativecommitment.